Bulbophyllum bidoupense and Schoenorchis hangianae—new species of orchids (Orchidaceae) from southern Vietnam - Nong, Duy Van; Averyanov, Leonid V. (Phytotaxa, 2015)
Bulbophyllum bidoupense (sect. Brachystachyae) and Schoenorchis hangianae (sect. Pumila) are described and illustrated as species new for science. Both species are local endemics of the Bidoup mountain system belonging to the South Annamese floristic province of the Indochinese floristic region within Lam Dong and Khanh Hoa provinces of southern Vietnam. Schoenorchis hangianae and allied S. scolopendria are rather isolated species recognized among their congeners by plagiotropic creeping plant habit.